A BRICK VERSION OF A THEOREM OF AUSLANDER. (5th March 2023) - SENTIERI, FRANCESCO
Abstract: We prove that a finite-dimensional algebra Λ is τ -tilting finite if and only if all the bricks over Λ are finitely generated. This is obtained as a consequence of the existence of proper locally maximal torsion classes for τ -tilting infinite algebras.